2019
DOI: 10.1016/j.dib.2019.103722
|View full text |Cite
|
Sign up to set email alerts
|

Data of H2O2 release from AQP8-knockdown rat hepatocyte mitochondria

Abstract: This article reports experimental data related to the research article entitled “Mitochondrial aquaporin-8 is involved in SREBP-controlled hepatocyte cholesterol biosynthesis” [Danielli et al., 2019]. We present data about hydrogen peroxide (H 2 O 2 ) release from mitochondria isolated from rat hepatocytes with or without silencing of aquaporin-8 (AQP8) protein expression. The rate of mitochondrial H 2 O 2 release (pmol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 3 publications
1
5
0
Order By: Relevance
“…As highlighted in the introduction section, S1R resides mainly at the interface mitochondrion associated membrane of the ER [24]. Moreover, AQP8 and AQP11 are localized in mitochondria [25,26] and ER [18] respectively, but ER can change is shape forming a reticular structure throughout the entire cytoplasm, thus enabling physical connections to other subcellular structures, such as the plasma membrane and mitochondria [53,54]. Results of co-localization experiments evidenced an intracellular localization of S1R [24] and AQP11 [32], while AQP3 and AQP8 were localized mainly on the plasma membrane.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…As highlighted in the introduction section, S1R resides mainly at the interface mitochondrion associated membrane of the ER [24]. Moreover, AQP8 and AQP11 are localized in mitochondria [25,26] and ER [18] respectively, but ER can change is shape forming a reticular structure throughout the entire cytoplasm, thus enabling physical connections to other subcellular structures, such as the plasma membrane and mitochondria [53,54]. Results of co-localization experiments evidenced an intracellular localization of S1R [24] and AQP11 [32], while AQP3 and AQP8 were localized mainly on the plasma membrane.…”
Section: Discussionmentioning
confidence: 91%
“…S1R is a chaperone protein, mainly expressed in mitochondria-associated endoplasmic reticulum (ER) membranes [24]. Interestingly, it has been demonstrated that also AQP8 and AQP11 are localized in mitochondria [25,26] and ER [18], respectively and possess H 2 O 2 permeability.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, mammalian AQP8 appears to have the largest H 2 O 2 permeability ( Bienert et al, 2007 ). Genetic manipulation of mitochondrial AQP8 supports its role in H 2 O 2 release to the cytosol ( Danielli et al, 2019a , b ), which could contribute to Cd-induced cell death.…”
Section: And Kidney Mitochondrial Damagementioning
confidence: 93%
“…Moving from these considerations, and prompted by the evidences that AQP8 and AQP11, are localized in mitochondria [42,43] and ER [15], respectively, in the present paper we studied the potential of S1R modulators as AQPs interfering compounds. As a first step we studied the in vitro effect of the well-established S1R agonists PRE-084 and RC-33 (both in its racemic and (R)-configured form), and of the S1R antagonist NE-100, on AQPs.…”
Section: Introductionmentioning
confidence: 97%